AGV dispatching and multi-agent simulation of container port - Zhao, Xiao Hui. (2008)
The dispatching and routing of AGVS (automatic guided vehicle system) in a container port is performed in a highly dynamic environment. Classical centralized AGVS have been studied for a long time and therea are commonly three main drawbacks: lack of robustness against failures, lack of flexibility and high computation time cost. These problems appear quite serious in a large-scale container port.